The Hub-and-Spoke Management of Glaucoma - Nuzzi, Raffaele; Marolo, Paola; Nuzzi, Alessia (Frontiers in Neuroscience, 2020)
Glaucoma is an extremely significant public health issue, since it is the most common cause of irreversible blindness worldwide, nevertheless it is still widely undiagnosed because of its devious nature. Glaucoma diagnosis criteria are well-defined and have to be strictly observed and recognized: the earlier the disease is diagnosed, the earlier the patient can undergo the most suitable treatment, the better can be the prognosis. The three levels of prevention are essential in the approach to the disease and its pathophysiological features make it eligible for screening. This review provides an overview of the current state of the art in glaucoma management, starting from its prevention and coming to the hub-and-spoke organization. This model applied to glaucoma aims to direct patients toward professional and not professional figures who may guide them in integrated care pathway. This path should be designed in accordance with best practice to coordinate glaucoma prevention, diagnosis, treatment and follow up with the best cost-benefit ratio, protecting both the interests of the patient and of the society.